Dehydrogenation of cyclohexane. - Viswanathan, S. (University of Ottawa (Canada), 1965)
The kinetics and mechanism of the dehydrogenation of cyclohexane to benzene over several supported and unsupported catalysts in the form of pellets and powders was studied in the temperature range of about 200 to 600°C in a flow system. Catalysts used inthe study included several commercial catalysts---platinum on alumina, palladium on alumina, cobalt oxide on alumina, nickel oxide, chromium oxide, and nickel oxide on alumina, and nickel oxide on kieselguhr (supplied by Girdler Co.) and nickel oxide powder and nickel oxide supported on pumice. The activatio energies (in k cals/mole) and frequency factors were found to be: nickel oxide powder - 13.7, 327.9; nichel oxide on pumice - 8.3, 14.6; nickel oxide on kieselghuhr - 5.7, 3.5; nickel oxide on alumina - 9.0, 50.9; nickel oxide, chromium oxide - 10.2, 17.4; platinum on alumina - 6.9, 35.8; and cobalt oxide on alumina - 21.7, 9623. The data obtained seemed to suggest that surface determined. It has been found that the rate data can be satisfactorily correlated by the equation: r=k&parl0;6HC p12-6HC p62&parr0;3 H&parl0;p K&parr0;&parl0;1+pC6H 12KC6H12 +pC6H6KC 6H6+pH2 KH2&parr0;2 &parl0;1&parr0;
Keywords: Engineering, Chemical.